Effect of Fast Annealing on Structural Characteristics and Optical Properties of Cu2ZnSnS4 Absorber Films Deposited by Doctor-Blade Technique - Hassanien, A. E.; Abdelhaleem, Soraya; Ahmad, Rameez; Schuster, Matthias; Moustafa, S. H.; Distaso, Monica; Peukert, Wolfgang; Wellmann, Peter (Journal of Nanoelectronics and Optoelectronics, 2019)
Cu2ZnSnS4 of kesterite structure is a non-toxic, earth-abundant and low-cost alternative for Cu (In, Ga)Se-2 compound due to its direct band gap of similar to 1.5 eV and absorption coefficient higher than 10(4) cm(-1). The thin CZTS films were prepared by the Doctor-Blade technique as a cheap, simple and suitable process for large-scale production. The ink of CZTS nanoparticles was synthesized by a solvothermal method and dispersed in chloroform before deposition on glass substrates. The effect of annealing conditions (temperature and time) on the structural characteristics (phase formation and grain size) and optical properties (band gap) of CZTS thin films was investigated. The elemental composition of the CZTS films was investigated by energy dispersive X-ray spectroscopy. The films, before and after annealing, are rich in sulfur, which decreases with the increase of annealing temperature as a result of its evaporation at high temperature. X-ray diffraction analysis and Raman scattering measurements confirm the formation of the crystalline tetragonal phase of CZTS. Values of the optical band gap were estimated using Tauc equation and optical transmission data. The band gap decreases from 2.10 eV to 1.23 eV and the grain grows from 4.6 nm to 38.8 nm as the annealing temperature ascends. The dependence of band gap energy on the grain size is verified, thus, the size of the grain can be used as a factor tuning the band-gap energy.
CRIS-Team WoS Importer:2019-08-30